2017 IEEE Working Conference on Software Visualization (VISSOFT) 2017
DOI: 10.1109/vissoft.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of the Medium in the Effectiveness of 3D Software Visualizations

Abstract: Many visualizations have proven to be effective in supporting various software related tasks. Although multiple media can be used to display a visualization, the standard computer screen is used the most. We hypothesize that the medium has a role in their effectiveness. We investigate our hypotheses by conducting a controlled user experiment. In the experiment we focus on the 3D city visualization technique used for software comprehension tasks. We deploy 3D city visualizations across a standard computer scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
1
24
1
2
Order By: Relevance
“…In our previous work, we included the medium as one of the dimensions of the proposed software visualization taxonomy. Although the authors of a previous taxonomy envisioned a future where software visualizations would use a variety of media (eg, head‐mounted displays), Table shows that only few studies that we found exploited this dimension (and that we analyzed in detail in a recent experiment). Almost 56% of the reviewed studies do not mention the expected medium on which the visualization should be displayed (labeled as not identified).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we included the medium as one of the dimensions of the proposed software visualization taxonomy. Although the authors of a previous taxonomy envisioned a future where software visualizations would use a variety of media (eg, head‐mounted displays), Table shows that only few studies that we found exploited this dimension (and that we analyzed in detail in a recent experiment). Almost 56% of the reviewed studies do not mention the expected medium on which the visualization should be displayed (labeled as not identified).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Donalek et al reported a better perception of the datascape geometry in graph visualizations when participants were immersed in VR [ 45 ]. Further benefits have been identified in terms of data validation [ 46 ], collaboration [ 45 ], increased task performance on specific data exploration tasks [ 47 , 48 ], and memorability [ 49 ]. Etemadpour et al found that especially surface-based visual encodings profited from a stereoscopic perception in VR [ 50 ].…”
Section: Related Workmentioning
confidence: 99%
“…Employing VR could be of particular benefit in such training scenarios, as trainees can enter the given surrounding and perceive them more realistically. Previous research points to advantages of virtual reality in terms of memorability [ 49 ], spatial navigation [ 70 ], orientation [ 71 ], learning performance on 3D models [ 41 ], and the understanding of complex geometries [ 44 ], which could also lead to an overall better training effect in the given context.…”
Section: Use Casesmentioning
confidence: 99%
“…They require developers to either use an application outside their development environment, or use a plug-in in their environment that sacrifices some valuable screen space. Amongst the few visualizations that use a different medium most are displayed in immersive virtual reality [9]. These visualizations require that developers completely change their development environment, and isolate themselves wearing a headset.…”
Section: Designmentioning
confidence: 99%